Accuracy and Reliability of 4D‐CT and Flexible Laryngoscopy in Upper Airway Evaluation in Robin Sequence. (13th July 2021) - Lam, Austin S.; Bindschadler, Michael D.; Evans, Kelly N.; Friedman, Seth D.; Blessing, Matthew S.; Bly, Randall; Cunningham, Michael L.; Egbert, Mark A.; Ettinger, Russell E.; Gallagher, Emily R.; Hopper, Richard A.; Johnson, Kaalan; et al.
Abstract : Objectives: To evaluate the performance of 4‐dimensional computed tomography (4D‐CT) in assessing upper airway obstruction (UAO) in patients with Robin sequence (RS) and compare the accuracy and reliability of 4D‐CT and flexible fiber‐optic laryngoscopy (FFL). Study Design: Prospective survey of retrospective clinical data. Setting: Single, tertiary care pediatric hospital. Methods: At initial and 30‐day time points, a multidisciplinary group of 11 clinicians who treat RS rated UAO severity in 32 sets of 4D‐CT visualizations and FFL videos (dynamic modalities) and static CT images. Raters assessed UAO at the velopharynx and oropharynx (1 = none to 5 = complete) and noted confidence levels of each rating. Intraclass correlation and Krippendorff alpha were used to assess intra‐ and interrater reliability, respectively. Accuracy was assessed by comparing clinician ratings with quantitative percentage constriction (QPC) ratings, calculated based on 4D‐CT airway cross‐sectional area. Results were compared using Wilcoxon rank‐sum and signed‐rank tests. Results: There was similar intrarater agreement (moderate to substantial) with 4D‐CT and FFL, and both demonstrated fair interrater agreement. Both modalities underestimated UAO severity, although 4D‐CT ratings were significantly more accurate, as determined by QPC similarity, than FFL (−1.06 and −1.46 vs QPC ratings, P =. 004). Overall confidence levels were similar for 4D‐CT and FFL, but other specialists were significantly less confident in FFL ratings than were otolaryngologists (2.25 and 3.92, P <. 0001). Conclusion: Although 4D‐CT may be more accurate in assessing the degree of UAO in patients with RS, 4D‐CT and FFL assessments demonstrate similar reliability. Additionally, 4D‐CT may be interpreted with greater confidence by nonotolaryngologists who care for these patients.